Reenvisioning Christian Ethics - Stephens, Darryl W. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Christian ethics is a wide and varied field; so diverse are the methods and approaches, theological perspectives and starting points, and scopes of inquiry and purposes-dare we even call it a discipline?-that the field is rarely considered as a whole. Christian ethics includes historical, descriptive, critical, constructive, and applied projects on countless topics. Lending creative energy to this field of study are a range of partner disciplines, including, most prominently, theology, philosophy, and sociology, each containing multiple schools themselves. To envision the entire field of Christian ethics is a difficult task; to reenvision the entire field may perhaps be impossible for one person. Thus, this publication includes original research by multiple scholars, each offering a distinct perspective from their primary partner discipline. Chapters include Roman Catholic and Protestant voices from Europe, Asia, and North America. In aggregate, these writings contribute to a composite reenvisioning of Christian ethics, refracting our collective vision through the prisms of diverse academic and methodological perspectives in this vast field of inquiry, study, and practice.